Effect of fungicides and phytoextracts on spore germination of Alternaria burnsii - Pipliwal, Sunil Kumar; Jadeja, K.B.; Sharma, Anshul; Dhakad, Jitendra (Annals of Agricultural Research, 2016)
An experiment was conducted on cumin crop and the treatment set of fungicides and phytoextractswere tested for their inhibitory effect on spore germination of Alternaria burnsii causing cumin blightwas performed in in vitro condition. In the laboratory screening of non systemic fungicides, mancozeb,zineb, ziram and chlorothalonil were found most effective in spore germination inhibition of A.burnsii. Among systemic fungicides, hexaconazole and tebuconazole were found most effective inthe reduction of spore germination of blight pathogens. Turmeric rhizome, garlic clove and gingerrhizome extracts proved to be the best sources of plant origin for the inhibition of spore germinationof blight pathogen.